Replacing the Father - Representing the Child. A Few Notes on the European History of Guardianship - Ighe, Ann (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
Fatherlessness seems to be a social problem of long historical continuance. In con-temporary social research we find numerous references to studies of the social effects of the absence of fathers. Divorces and new ways to structure sexual relations are, at least in Europe of today, more common reasons for this than loss through death. However, in the long histori-cal period addressed by this publication, 1100 – 1900, there are some specific social, demo-graphic, economic and even biological features that clearly distinguish these past societies from Europe of the present day. The immense importance connected to a person’s belonging to and position within a household is one of them. A much higher mortality rate is another. Young children constituted an age group among whom the death rate was especially high. But young children were also much more often exposed to the loss of one or both parents com-pared with today. Due to this restructured families through remarriage were very common. So was single parent families headed by widows. However, the breaking up of families through the death of a father was often balanced by a partial, formal restructuring of the family, putting someone else in the father’s place even when remarriage did not occur. To make an overview of this particular kind of guardianship, when and how someone in the legal sense replaces the father to represent the child, is the focus of this article. Regulating the succession of guardianship over children was an important task for families, kinship networks and more public institutions, especially the legal sphere, throughout this long period. Nevertheless, it is not easy to even try to tell a story covering all of Europe for so many centuries. A few notes are the most that can be achieved here, with the ambition to initiate a comparative and overriding discussion of these matters.